Reasons for referral, intervention approaches and demographic characteristics of clients with intellectual disability attending adult psychiatric outpatient services in the Kingdom of Bahrain. (10th September 2013) - Grey, I.; Al‐Saihati, B. A.; Al‐Haddad, M.; McClean, B.
Abstract Background Relatively little information is available regarding the use of psychiatric services by individuals with intellectual disability (ID) in Arab countries. The current study aimed to identify (1) the reasons for referral; (2) demographic characteristics of individuals referred; (3) previous contact with child psychiatric services; (4) psychiatric diagnoses; (5) level of ID; (6) nature of interventions; and (7) patterns of medication usage in individuals attending a specialist psychiatric service for individuals with an ID in the Kingdom of Bahrain. Method Case file analysis was used. Files that recorded attendance at the specialist service within a specific calendar year were selected. A total of 537 files were available for review and 79 contained records indicating the individual had been seen within the year. Results The primary referral reason to adult psychiatric services was the presence of behavioural disturbance. Pharmacological intervention was the dominant treatment choice and no individual was recommended for psychological/behavioural intervention. Psychiatric diagnosis was not recorded in over 90% of cases. Conclusion Services in the Kingdom of Bahrain for individuals with ID rely exclusively on pharmacological approaches for the treatment of behavioural disorders. Implications for best practice guidelines are discussed.